Asymmetric synthesis of benzothiazolopyrimidines with high catalytic efficiency and stereoselectivity under bifunctional phosphonium salt systems. Issue 76 (21st August 2020) - Lu, Dongming; Wu, Jia-Hong; Pan, Jianke; Chen, Xue; Ren, Xiaoyu; Wang, Tianli
Abstract : Bifunctional phosphonium salt-mediated formal [4+2] annulation towards chiral benzothiazolopyrimidine compounds with excellent yields and stereoselectivities. Abstract : An efficient formal [4+2] annulation between 2-benzothiazolimines and allenoates mediated by an amino acid-derived bifunctional phosphonium salt catalyst is developed. This protocol provides a new and facile synthetic approach to create a broad range of isothiourea-based benzothiazolopyrimidine derivatives under mild reaction conditions with high isolated yields and excellent diastereo- and enantioselectivities.